Smoothing the Power Output of a Wind Turbine Group with a Compensation Strategy of Power Variation - Chung, P. D. (Engineering, Technology & Applied Science Research, 2021)
This paper proposes a new scheme to reduce the output power variation range of a wind turbine group without an energy storage system. This proposal is based on the active power compensation principle for each wind turbine. In this research, the wind turbine operates in the active power control mode. The reference active power is calculated in such a way that it compensates for the difference between the average output power and the actual output power. To verify and evaluate the proposed method, we simulated a group of two 1.5MW-wind turbines in the Simulink environment of MATLAB. Simulation results were compared to the ones of a wind turbine group without any smoothing scheme and the ones of the same group with the Exponential Moving Average method. From this comparison, we can conclude that with the proposed method, the actual output power of the wind turbine group becomes smoother than that of the wind turbine group without any smoothing scheme. Moreover, the performance of the wind turbine group with the proposed method is better than that of the wind turbine group with the Exponential Moving Average method.